Influence of necking configuration of a methanol steam reformer on catalyst amount and reforming performance. Issue 2 (15th June 2022) - Perng, Shiang-Wuu; Horng, Rong-Fang; Wu, Horng-Wen
ABSTRACT: A reformer applied in a PEM (proton exchange membrane) fuel cell, which is a clean power source, is becoming a future trend as it employs catalyst to produce hydrogen. If some of the catalyst can be saved, the saved catalyst can be used to produce the extra hydrogen to generate the increased power of PEM fuel cell. The main objective of this study is then to investigate the saved catalyst amount in the cylindrical methanol reformer by the necking configuration through the non-isothermal transport processes and the estimated net power of PEM fuel cell produced by the saved catalyst. The results show that the used catalyst compared with the original reformer is saved by about 23.44%, and the saved catalyst can be used to produce additional amount of hydrogen to increase about 14.78% estimated net power of PEM fuel cell. The results of calculation were also compared with those of experiments, and achieved very good approximation.